Dolly Parton's Heartstrings [videorecording (DVD)] - Parton, Dolly; Turner, Kathleen, 1954-; Goodwin, Ginnifer; Bornheimer, Kyle, 1975-; Crumley, Tyle; Donnelly Haskell, Mary; Amatrudo, Ed; Burke, Delta; Lawson, Ben, 1980-; Elliott, Brooke; Weaver, Michele; Reid, Tim, 1944-; et al. (Warner Bros. Entertainment Inc., 2022)
An anthology series that showcases the stories, memories and inspirations behind Dolly Parton's most beloved songs. New and classic Dolly music will score every episode. Each story will vary in tone, from love stories and inspirational tales to family dramas, westerns and revenge comedies.